A critical review on definitions, indices, and uncertainty characterization in resiliency‐oriented operation of power systems. (1st November 2020) - Izadi, Mehdi; Hosseinian, Seyed Hossein; Dehghan, Shahab; Fakharian, Ahmad; Amjady, Nima
Abstract: Disastrous and hazardous events (eg, natural disasters and cyber‐physical attacks) have significantly increased in power systems, which drastically affect their performance. Different research works have been recently introduced in the literature, aiming at thoroughly evaluating power system resilience against various types of disastrous and hazardous events. In this article, a review of these research works is presented. Moreover, the main differences between the concept of resiliency and the concepts of accessibility, durability, flexibility, hardening, maintainability, reliability, stability, survivability, sustainability, and vulnerability are described. Additionally, various resiliency indices are presented, and different techniques to increase power system resilience against disastrous and hazardous events are reviewed. Furthermore, uncertainty handling approaches used in the literature to analyze power system resiliency are discussed. Some concluding remarks are also presented. Abstract : This article presents a critical review of definitions, indices, and enhancing methods for power system resiliency with focusing on different uncertainty modeling techniques.